2020
DOI: 10.1111/jfpp.14864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high hydrostatic pressure processing on phytochemicals, antioxidant activity, and behavior ofBotrytis cinereain white grape juice concentrate

Abstract: Grape and its derived products contain a wide range of polyphenolic compounds that have been shown to possess anti-inflammatory activities, and to prevent cellular deterioration that predisposes to atherosclerosis and coronary heart disease, therefore, these compounds are considered as bioactive compounds having beneficial effects on human health (Rasines-Perea & Teissedre, 2017; Zuanazzi et al., 2019). Moreover, the compounds found in grape and its by-products have positive effects on health and can be found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 76 publications
(130 reference statements)
1
9
0
Order By: Relevance
“…Chang et al 35 emphasized that higher phenolic contents of 25.26 and 26.81 mg/mL were determined after HHP application at 300 and 600 MPa for 3 min at 20 °C in comparison with the control (23.47 mg/mL) and also there was no important effect of pressurization on the anthocyanin content. In addition to a previous study, Torres-Ossandoń et al 23 mentioned for white grape juice that an increase of phenolic content was observed after all application conditions of HHP (200, 300, 400 MPa; 2, 4 min; 20 °C), but this increase at levels above 300 MPa for 2 min in terms of antioxidant retention. However, in the study performed on wine, the maximum anthocyanin level was reached at the lowest pressure level (200 MPa; 20 °C; 10 min).…”
Section: ■ Results and Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Chang et al 35 emphasized that higher phenolic contents of 25.26 and 26.81 mg/mL were determined after HHP application at 300 and 600 MPa for 3 min at 20 °C in comparison with the control (23.47 mg/mL) and also there was no important effect of pressurization on the anthocyanin content. In addition to a previous study, Torres-Ossandoń et al 23 mentioned for white grape juice that an increase of phenolic content was observed after all application conditions of HHP (200, 300, 400 MPa; 2, 4 min; 20 °C), but this increase at levels above 300 MPa for 2 min in terms of antioxidant retention. However, in the study performed on wine, the maximum anthocyanin level was reached at the lowest pressure level (200 MPa; 20 °C; 10 min).…”
Section: ■ Results and Discussionmentioning
confidence: 49%
“…In other words, in terms of the TMAC values, it was concluded that there were losses in general. Torres-Ossandoń et al 23 reported for grape juice concentrate that there were no significant differences between HHP-treated samples and control samples at 200, 300, and 400 MPa for 2 and 4 min at room temperature in terms of the total flavonoid content. In the study of citrus-maqui beverages, minor statistically important changes in the flavonoid levels and slightly lower levels of anthocyanin contents were observed after treatment at 450 and 600 MPa for 3 min at 20 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In white grape juice concentrate, several authors [ 145 ] found that pressurization caused a decrease in total flavonoids and TPC: 8% and 25%, respectively, after 35 days of storage (4 °C). HPP caused a slight but significant decrease of both ORAC and DPPH values compared to the control samples.…”
Section: Impact Of Hpp On Antioxidant Activity During Storage Of Fruits and Fruit Productsmentioning
confidence: 99%
“… A decrease of 15.8% and 7.5% was observed in HPP samples at zero days and after 35 days, respectively. [ 145 ] *: refrigerated storage; HPP: High Pressure Processing; TP: Thermal Processing; UF: Ultrafiltration; HPCD: High Pressure Carbon Dioxide; PLA: Polylactic acid; PET: Polyethyleneterephthalate; US: Ultrasound; TPC: Total phenol content; HPLC-DAD: High performance liquid chromatography-Diodes array detector; GAE: Gallic acid equivalent; CGE: Cyanidin-3-glucoside equivalent; AA: Ascorbic acid. …”
Section: Impact Of Hpp On Antioxidant Activity During Storage Of Fruits and Fruit Productsmentioning
confidence: 99%